Progression of site-specific recurrence of pancreatic cancer and implications for treatment - Rompen, Ingmar F.; Levine, Jonah; Habib, Joseph R.; Sereni, Elisabetta; Mughal, Nabiha; Hewitt, Daniel Brock; Sacks, Greg D.; Welling, Theodore H.; Simeone, Diane M.; Kaplan, Brian; Berman, Russell S.; Cohen, Steven M.; et al. (Annals of surgery, 2024)
Objective: To analyze postrecurrence progression in the context of recurrence sites and assess implications for postrecurrence treatment. - Background: Most patients with resected pancreatic ductal adenocarcinoma (PDAC) recur within 2 years. Different survival outcomes for location-specific patterns of recurrence are reported, highlighting their prognostic value. However, a lack of understanding of postrecurrence progression and survival remains. - Methods: This retrospective analysis included surgically treated patients with PDAC at NYU Langone Health (2010-2021). Sites of recurrence were identified at the time of diagnosis and further follow-up. Kaplan-Meier curves, log-rank test, and Cox regression analyses were applied to assess survival outcomes. - Results: Recurrence occurred in 57.3% (196/342) patients with a median time to recurrence of 11.3 months (95% CI: 12.6-16.5). The first site of recurrence was local in 43.9% of patients, liver in 23.5%, peritoneal in 8.7%, lung in 3.6%, whereas 20.4% had multiple sites of recurrence. Progression to secondary sites was observed in 11.7%. Only lung involvement was associated with significantly longer survival after recurrence compared with other sites (16.9 vs 8.49 months, P = 0.003). In local recurrence, 21 (33.3%) patients were alive after 1 year without progression to secondary sites. This was associated with a CA19-9 of <100 U/mL at the time of primary diagnosis (P = 0.039), nodal negative disease (P = 0.023), and well-moderate differentiation (P = 0.042) compared with patients with progression. - Conclusion: Except for lung recurrence, postrecurrence survival after PDAC resection is associated with poor survival. A subset of patients with local-only recurrence do not quickly succumb to systemic spread. This is associated with markers for favorable tumor biology, making them candidates for potential curative re-resections when feasible.